The Effect Of The Implementation Of E-Performance Assessment, Work Environment, Competence, And Motivation On Employee Performance In The Health Office Of Mesuji District - Juwita Diniati Pasaribu; Tina Miniawati Virgawenda Barusman (International Journal of Economics, Business and Innovation Research, 2026)
This study aims to analyze the effect of the implementation of the E-Performance System, work environment, competence, and work motivation on employee performance at the Mesuji District Health Office. Employee performance is an important factor in supporting the success of health service delivery, so effective, professional, and performance-based human resource management is needed. The research method used is a quantitative method with a survey approach. The population in this study were all employees of the Mesuji District Health Office with a sampling technique using the census method (total sampling). Data were collected through questionnaires and analyzed using multiple linear regression analysis. Hypothesis testing was carried out through partial tests (t-tests) to determine the effect of each independent variable on employee performance. The results showed that the implementation of the E-Performance System had a positive and significant effect on employee performance with a calculated t value of 3.118 and a significance of 0.003. The work environment also had a positive and significant effect on employee performance with a calculated t value of 2.334 and a significance of 0.023. Competence had a positive and significant effect on employee performance with a calculated t value of 1.198 and a significance of 0.039. In addition, work motivation showed a positive and significant influence on employee performance with a t-value of 2.380 and a significance of 0.025. The implications of this study confirm that strengthening the implementation of the E-Performance System, improving and organizing the work environment, developing employee competencies on an ongoing basis, and increasing work motivation are important factors in improving employee performance at the Mesuji District Health Office. The results of this study are expected to be a consideration for leaders in formulating human resource management policies to improve the quality of health services to the community.